Pengaruh Penggunaan Media Pembelajaran Terhadap Tingkat Financial Knowledge Siswa - Rahma Dila Safitri; Efni Cerya (Universitas Negeri Padang, 2021)
This research aimed to find to find out whether there was the effect of learning media on the level of financial knowledge of students. The kind of this reseacrh was quasi-experimental reseacrh. The quasi-experimental design used was a pretest posttest control group design. The media used in this study is the Fillecya (Financial literacy) Board. The population of this study was all X IPS classes of SMA N 2 Lubuk Basung in academic year 2019/2020 consisting of five classes. The researcher took two classes as the sample, they were X IPS 1 and X IPS 2 as the experimental and control class in this research. In the experimental class the value of the level of financial knowledge of students was 81.97 and the increase in the average value of the level of financial knowledge was 25.44 with an N gain of 0.57 (medium category). In the control class the value of the financial literacy level of students is 68.83 and the increase in the average value of financial literacy levels is 21.60 with an N gain of 0.40 (medium category). Based on the t test, it showed that the value of sig. 0,000 <0.05, so it can be summarized that 1) instructional media influenced the level of financial knowledge of students, 2) there were differences in the level of financial knowledge before and after learning by using fillecya board learning media, 3) there were some differences in the level of financial knowledge before and after learning without using learning media (conventional).Keywords: fillecya board, financial knowledge